Home page for accesible maths 1 1 Further Integration

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

1.24 Example continued

Thus we have to integrate 1x-1\frac{1}{x-1} and 2x+2x2+9\frac{2x+2}{x^{2}+9}. The integral of the first term is just log|x-1|+c\log|x-1|+c.

We further split the second term into 2xx2+9\frac{2x}{x^{2}+9} and 2x2+9\frac{2}{x^{2}+9}. For the first of these, we make the substitution u=x2+9u={x^{2}+9} to obtain that the integral is log(x2+9)+c\log(x^{2}+9)+c^{\prime}.

For the second, we substitute x=3tantx={3\tan t} to obtain the integral

2dxx2+9=23tan-1x3+c′′.\int\frac{2\,dx}{x^{2}+9}={\frac{2}{3}\tan^{-1}\frac{x}{3}+c^{\prime\prime}.}

Putting all of these together, we obtain:

3x2+7(x-1)(x2+9)dx=log|x-1|+log(x2+9)+23tan-1x3+C.\int\frac{3x^{2}+7}{(x-1)(x^{2}+9)}\,dx=\,{\log|x-1|+\log(x^{2}+9)+\frac{2}{3}% \tan^{-1}\frac{x}{3}+C.}